An optimized multi-modular resonant switched capacitor converter. Issue 1 (1st December 2022) - Li, Ruishu; Chang, Xiao; Han, Xiaoqing; He, Xin; Guo, Zhuoyan; Meng, Runquan
Abstract: The switched capacitor converters have the advantages of high efficiency and high power density, which are widely used in data centers, distributed photovoltaic power generation, and other fields. In this paper, an optimized multi-modular resonant switched capacitor converter (MMRSCC) is proposed for an intermediate bus converter in the power supply system of data centers. By removing the inductance of part of the coupled resonant circuit, the converter can eliminate the influence of the parameter difference of passive components, and no additional voltage clamp circuit is needed, which improves the power density. At the same time, the half-bridge with the same switching action on the rectifier side is combined into one, which reduces the number of switching devices and is more conducive to improving the voltage conversion efficiency. In addition, the inductor of the basic unit of the resonant switched capacitor with the same state is shared to reduce the volume of the passive device, further improve the power density, and optimize the MMRSCC. Finally, the correctness of the topology is verified by simulation on the PLECS.